Faktor sosial ekonomi yang mempengaruhi mobilitas migran (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
This study aims to determine any socio-economic factors that can affect the mobility of migrants in the city of Samarinda. the increasing mobility of migrants in the city of Samarinda suspected there were other factors in addition to economic factors but also geographical factors Samarinda is the City with a good level of infrastructure development and a fairly modern city. So this is one reason semangkin increasing flow of migrant mobility in the city of Samarinda. This study aimed to determine the socio-economic factors mobility of migrants in the city of Samarinda. Reasons that encourage migrants to the city of Samarinda, the reasons that attracted migrants in the city of Samarinda, the purpose of migrant mobility in the city of Samarinda, sex and age of migrants, status of residence, place of origin, the last educational status, type of job you have. Analysis of the mobility of migrants in the city of Samarinda is analyzed using quantitative research methods and analysis in this study using binary logistic regression While socio-economic indicators were analyzed using descriptive statistics. The results of the analysis of Logistic Regression Model to explain the factors that affect the mobility of migrants in the city of Samarinda is marital status with a significance value (0,048) and work with signifiknsi value (0.006). Economically it is clear that the behavior of the respondents in this study tended to to migrate with the aim to improve the lives of their families.